The program of social and psychological support for unemployed citizens - Місячна, Н. М. (Київський національний університет імені Тараса Шевченка, 2018)
The article discusses the problems of social and psychological readiness of unemployed people to change their professions and to be retrained. The performed theoretical and methodological analysis of national and foreign literature has allowed us to determine structural components of psychological readiness: motivational, orientation, cognitive and emotional-volitional. Namely these structural components have created the basis of the theoretical model of unemployed people psychological readiness to change their professions and to be retrained. The motivational component includes the following aspects: working conditions, rewards, aspiration for achievement, self-improvement or changes, power and influence, relationships. Orientation component includes the following aspects: focus on self-changes (changes of professional self-concept), on new relationships, and on new tasks. The cognitive component includes the following aspects: the ability to realize their knowledge and skills in the future profession; openness to new knowledge; the ability to acquire new knowledge; self-development. The emotional-volitional component includes the following aspects: emotional stability, social courage, self-control, spontaneity, perseverance, ability to succeed in spite of obstacles. The empirical research was conducted in order to study the social-psychological readiness of unemployed citizens and internally displaced people. Based on the results obtained, a number of social-psychological barriers affecting unemployed citizens’ readiness have been identified, in particular, low aspirations for personal and professional development, low achievement motivation, high tension, irritability due to existing dissatisfied needs and unrealized goals. Not all their actions are appropriate, sometimes unemployed people are prone to useless pastime. That is why the improved program of social and psychological support for unemployed citizens was used. Comparison of the research result for the unemployed at different stages (initial, final) of the forming experiment has allowed us to assert that the proposed program is an effective method for forming influence and correction of its participants’ personal traits. Its use allows the participants to work out and understand personal limitations that reduce social and psychological readiness of the unemployed.

У статті висвітлено проблематику соціально-психологічної готовності безробітних до зміни професії та перенавчання. Теоретико-методологічний аналіз вітчизняної та зарубіжної літератури дозволив виокремити структурні компоненти психологічної готовності: мотиваційний, орієнтаційний, пізнавальний та емоційно-вольовий. Саме ці структурні компоненти покладені в основу теоретичної моделі психологічної готовності безробітних до зміни професії та перенавчання. До мотиваційного компоненту включено такі складові: умови праці, винагорода, прагнення до досягнень, до самовдосконалення, до змін, влада та впливовість, взаємини. Складовими орієнтаційного компоненту є: спрямованість на зміну себе (зміна професійної Я-концепції), на встановлення нових стосунків, на виконання нових завдань. До когнітивного компоненту ввійшли такі складові: можливість реалізувати свої знання, вміння, навички в майбутній професії; відкритість до нових знань; налаштованість на засвоєння нових знань; саморозвиток. Складові емоційно-вольового компоненту: емоційна стабільність, соціальна сміливість, самоконтроль, спонтанність, наполегливість, вміння досягати успіху незважаючи на перешкоди. З метою вивчення соціально-психологічної готовності безробітних громадян та вимушених переселенців проводилося емпіричне дослідження. На підставі одержаних результатів виявлено низку соціально-психологічних бар’єрів, що впливають на рівень готовності безробітних, зокрема, це низький рівень прагнень до особистісного і професійного розвитку, низький рівень мотивації досягнення, високий рівень напруженості, дратівливості, що зумовлений наявністю незадоволених потреб і нереалізованих цілей. Не всі дії доцільні, іноді безробітні схильні до марного проведення часу. Саме тому використовувалася удосконалена програма соціально-психологічної підтримки безробітних громадян. Порівняння зрізів на різних етапах формувального експерименту (початковому, завершальному) в експериментальних групах безробітних дозволяє стверджувати, що запропонована програма є ефективним та дієвим методом формувального впливу та коригування особистісних якостей її учасників. Її використання дозволяє на суттєвому рівні опрацювати та усвідомити суб’єктивні обмеження, які знижують рівень соціально-психологічної готовності безробітних.
Програма соціально-психологічної підтримки безробітних громадян
Keywords: unemployment; psychological readiness; psychological barriers; professional orientation; social-psychological support; training; group work; безробіття; психологічна готовність; психологічні бар’єри; професійна орієнтація; соціально-психологічна підтримка; тренінг; групова робота